Three tainted teas - Cahoon, Lynn (Cahoon, Lynn. Kitchen witch mysteries, 2022)
"Business is bubbling at Mia's catering service and cooking school, Mia's Morsels, but toil and trouble are not far behind. Mia just accepted her toughest gig yet: last-minute wedding planner for Magic Springs' own Romeo and Juliet. Though the small town is fairly accepting of magic, two families have been locked in a vicious feud spanning generations. Unfortunately for both families, they're about to become in-laws! Amethyst and Tok are excited to wed in a few weeks and somehow Mia must ensure the event is flawless. But when she goes to pick up paperwork from the couple's previous wedding planner, Mia discovers the woman murdered in an apparent attempt to stop the contentious union. Now, not only is Mia a prime suspect, as the new planner she may also be the killer's next target. Backed by her squad, her charms--literal and figurative--and a protective amulet from her Grans, it's up to Mia to save the star-crossed couple's wedding, her professional reputation ... and maybe even her life!"--